In response to Fleiss et al. (2022), climate change will affect palm oil yields in Malaysia very detrimentally by 2100 and less so before that date - R. R. M. Paterson (CABI Agriculture and Bioscience)
Abstract Fleiss et al. (CABI Agri Biosci 3:59, 2022) suggest that palm oil yield from Malaysia oil palm will not be affected substantially by increased temperature from climate change with evidence from a misinterpretation of a paper co-authored by the current author. This current comment article provides evidence that suggest that yields will be much lower in the future.